On the chemical composition, microstructure and mechanical properties of a Nitrogen-contaminated Ti-6Al-4V component built by Wire-Arc Additive Manufacturing - Hu, Dongchen; Biswal, Romali; Sahu, Vivek K.; Fellowes, Jonathan W.; Zadehkabir, A.; Williams, Stewart W.; Davis, Alec E. (IOP Publishing, 2024)
Additive manufacturing (AM) using recycled Ti-6Al-4V (Ti64) feedstock material from wrought waste streams is a novel process that can reduce the overall energy cost and carbon (CO2) footprint when compared to primary-production routes. The potential contamination of recycled feedstock material (e.g. C, O, N and Fe) can affect the microstructure and mechanical properties of the component. In this work, a Ti64 test wall built using wire arc AM (WAAM) was studied, where the top half only was contaminated by N through the shielding gas during deposition. This allowed a direct comparison of Ti64 WAAM material with high and low N content, deposited under otherwise identical conditions, to replicate the worst-case scenario of N contamination from using recycled swarf. The hardness of the N-contaminated section was found to be 25% higher than the uncontaminated section of the wall, demonstrating the N solid solution strengthening in Ti64. The room temperature transformed microstructure was found to have a 25% coarser α-lath thickness, which was proposed to be an effect of the AM cyclical heating and increasing of the β-transus temperature due to a higher level of N. Additionally, the outer layer of the N-contaminated sample section was found to have a refined parent β grain structure.
44th Risø International Symposium on Materials Science (RISO 2024) 2-6 September 2024, Roskilde, Denmark
Keywords: 4014 Manufacturing Engineering; 40 Engineering; 12 Responsible Consumption and Production